Gender differences in early-career wage growth - Sami Napari (The Research Institute of the Finnish Economy (ETLA), 2007)
In Finnish manufacturing, the gender wage gap more than doubles during the first ten years in the labor market. This paper studies the factors contributing to the gender gap in early-career wage growth. The analysis shows that the size of the gender gap in wage growth varies with mobility status the gap being much higher when changing employers compared to within-firm wage growth. Several explanations for the gender gap in wage growth based on human capital theory and theory of compensating wage differentials are considered. However, most of the gap in wage growth remains unexplained. Further analysis documents that the female penalty in wage growth increases significantly as we move along the conditional wage growth distribution with a sharp acceleration in the gap at the top of the distribution.
Keywords: J24; J31; J6; J7; 330; Gender Wage Gap; Wage Growth; Mobility; Lohndifferenzierung; Berufseinstieg; Erwerbsverlauf; Geschlecht; Humankapital; Verarbeitendes Gewerbe; Finnland